Gene Expression Profiling during Conidiation in the Rice Blast Pathogen Magnaporthe oryzae - Kim, Kyoung Su; Lee, Yong-Hwan (PLOS ONE, 2012)
Conidiation of phytopathogenic fungi is a key developmental process that plays a central role in their life cycles and in epidemics. However, there is little information on conidiation-induced molecular changes in the rice blast fungus Magnaporthe oryzae. As a first step to understand conidiogenesis in this fungus, we measured genome-wide gene expression profiles during conidiation using a whole genome oligonucleotide microarray. At a two-fold expression difference, approximately 4.42% and 4.08% of genes were upregulated and downregulated, respectively, during conidiation. The differentially expressed genes were functionally categorized by gene ontology (GO) term analysis, which demonstrated that the gene set encoded proteins that function in metabolism, cell wall biosynthesis, transcription, and molecule transport. To define the events of the complicated process of conidiogenesis, another set of microarray experiments was performed using a deletion mutant for MoHOX2, a stage-specific transcriptional regulator essential for conidial formation, which was expressed de novo in a conidiation-specific manner in M. oryzae. Gene expression profiles were compared between the wild-type and the ΔMohox2 mutant during conidiation. This analysis defined a common gene set that was upregulated in the wild-type and downregulated in the ΔMohox2 mutant during conidiation; this gene set is expected to include conidiation-related downstream genes of MoHOX2. We identified several hundred genes that are differentially-expressed during conidiation; our results serve as an important resource for understanding the conidiation, a process in M. oryzae, which is critical for disease development.